Collaborative Learning: Theoretical Foundations and Applicable Strategies to University Teaching - Roselli, Nestor D. (2016)
Collaborative learning is a construct that identifies a current strong field, both in face-to-face and virtual education. Firstly, three converging theoretical sources are analyzed: socio-cognitive conflict theory, intersubjectivity theory and distributed cognition theory. Secondly, a model of strategies that can be implemented by teachers to develop socio-cognitive collaboration is presented. This model integrates and systematizes several academic group animation techniques developed within the collaborative learning field. These integrated techniques, within a coherent and unified didactic intention, allow talking more about strategies than independent and dissociated techniques. Each strategy is specifically described, which refers to six areas: encouragement of dialogue, listening to others and reciprocal assessment; collaboration for negotiation and consensus building; activity organization; study and appropriation of bibliographic information; conceptual development; collective writing. These strategies proposed (designed to stimulate the collaboration between 2, 4 and exceptionally, 6 or 8 students) are not the only possible strategies, they can be combined with the ones the teacher might suggest. The strict pattern of each strategy is a characteristic of the proposal. The teacher is also encouraged to benchmark the results obtained using each strategy and those obtained using individual or non-collaborative strategies. Finally, conclusions and recommendations for the implementation of these strategies are discussed.